Changes in organic matter and in microbial biomass of a natural forest soil under different management - Júnior, Milton Marchiori; Melo, Wanderley José de (Pesquisa Agropecuaria Brasileira, 2000)
The effect of soil management on forms of carbon and microbial biomass was studied in a Typic Euthortox soil. The treatments tested were: natural forest; natural forest till 1976 and coffee till 1994 (sampling on the shoot projection and between lines ); natural forest till 1976, coffee till 1991 and corn till 1994; natural forest till 1940, coffee till 1960, citrus till 1978 and sugar cane till 1994 (sampling on the planting line and between lines ). The treatment with sugar cane presented the largest values of microbial carbon in relation to the natural forest. The agricultural management of soil increased the percentage of organic carbon in humic and fulvic acids forms. The soil presented more than 74% of organic carbon in the form of residual humus.